Impact of the National Health Insurance Authority-Health Maintenance Organisation Authorisation code system on the knowledge, attitude, and practice related to hypertension among National Health Insurance Authority-enrolled outpatients in a tertiary hospital, Federal Capital Territory - Marvellous Nonye Aniche; Zainab Abubakar Galadima; Josephine O. Abiri; Muhammed Garba; Esther Haruna Michael; Idoko Agumage; Abubakar Mustapha Danraka (Journal of Biomedical & Clinical Research)
Background: Hypertension is a globally significant health burden, with a prevalence rate of nearly 49%. However, the clinical and economic burden is high and continues to increase. The NHIA, in partnership with HMOs in a bid to mitigate the financial burden on Nigerians, has in some way been beneficial. The delivery of universal health coverage through this integration involves a chain of processes, including acquiring a Pharmacy Authorization Code to obtain medications to improve the quality of life. However, with the implementation of a monthly authorization code process, the impact on the KAP of hypertensive outpatients (towards hypertension management) enrolled in the insurance scheme is limited. This study assessed the impact of the NHIA-HMO pharmacy authorization code (PAC) system on the KAP of hypertension in NHIA-enrolled outpatients within UATH. It also seeks to identify potential barriers within the coding system.Method: A cross-sectional study using a mixed-method approach was conducted with 345 hypertensive patients aged 18 years and above at UATH, Gwagwalada. A random sampling technique was used for the quantitative study, and data was collected through a validated, semi-structured questionnaire covering socio-demographics, KAP levels, and perceptions of the impact of the code system. The qualitative component utilized a pre-tested interview guide administered to purposively selected participants. Quantitative data was analyzed using SPSS (v27.02), while qualitative data underwent thematic analysis with visualization using ATLAS.TI (v25) and MS EXCEL (2019).Result: Correlation and regression analyses showed that the NHIA-HMO Code significantly influenced attitude and practice (r = 0.227, p < 0.001; r = 0.252, p < 0.001) but had no impact on knowledge (r = -0.023, p = 0.336). The regression model indicated that the code system predicts changes in attitude and practice but explains only 8.3% and 11.7% of their variance, suggesting other influencing factors. Emerging qualitative themes such as "difficulty obtaining the code," "long waiting hours," and "lack of HMO communication" highlight systemic challenges, whereas facilitators like "improved adherence, follow-up, and patient counseling" demonstrate its potential benefits.Conclusion: The NHIA-HMO code system does not enhance knowledge about hypertension but significantly influences attitude and practice, encouraging medication adherence. However, bureaucratic delays hinder its effectiveness. Additionally, long-term NHIS enrollment or HMO selection does not necessarily translate to improved KAP.